Goat milk whey fermentation: A sustainable approach to producing tryptophan functional beverages by lactobacillus rhamnosus and lactobacillus casei - Cahyanti, Antonia Nani; Legowo, Anang Mohamad; Rizqiati, Heni; Harjanti, Dian Wahyu; Sari, Anisa Rachma (Journal of Advanced Veterinary Research, 2025)
The challenge of sustainable goat milk processing can be partially overcome by utilizing the nutrients in whey to create functional foods that can improve health. This encourages the utilization of nutrients in goat milk whey through fermentation by utilizing microbes to produce bioactive compounds, one of them is tryptophan. Protein in whey one of which is lactalbumin, rich in the essential amino acid tryptophan. This study examines the fermentation of goat milk whey using L. rhamnosus and L. casei, to assess tryptophan levels, along with chemical and microbiological properties Sweet whey was produced by using rennet, centrifugated and filtrated, then inoculated with these bacteria according to the treatment (L. rhamnosus : L. casei = 1:0; 0:1; 1:1). Incubation occurred at 37℃ for a duration of 24 hours. The results showed that starter culture affects significantly (P<0.05) to lactose, pH, crude protein and crude tryptophan; but did not affects significantly (P>0.05) to titratable acidity and lactic acid bacteria count. In conclusion, fermented whey contained nearly lactose 3.39%-4.41%; pH 3.94-4.00; acidity 0.06%-0,11%; lactic acid bacteria count 9.55-9.89 log CFU/ml; crude protein 12.24%-19.57% and crude tryptophan 89.72 - 113.98 mg/100mg.